ANALISIS KINERJA KEUANGAN BADAN PENDAPATAN DAERAH KABUPATEN KOLAKA TAHUN 2021-2023 - Hidayah, Anita Rahmah; Triani, Neks; Chairunnas, Arnadi (Komunitas Manajemen Kompetitif, 2025)
This study aims to analyze the financial performance of the Regional Revenue Agency (Bapenda) of Kolaka Regency during the 2021–2023 period. The research adopts a quantitative descriptive approach, utilizing secondary data in the form of regional revenue budget realization reports obtained from Bapenda Kolaka Regency.The findings indicate that the region’s financial independence remains within a low to moderate category, reflecting a high dependency on from the central government. The effectiveness ratio of Regional Original Revenue (PAD) shows a relatively favorable trend transfers, particularly in 2022, when PAD realization exceeded the predetermined target. However, this performance declined again in 2023.Furthermore, the growth ratio suggests that the region’s capacity to enhance financial performance has been inconsistent from year to year. These results highlight the necessity for Bapenda Kolaka Regency to optimize and diversify existing revenue streams. Additionally, improving the efficiency and effectiveness of regional financial management should be a critical focus. Keywords: Keywords: Financial performance, independence ratio, effectiveness ratio, growth ratio, local revenue, Bapenda Kolaka.